Vulnerabilities and Human Rights Violations Based on the Global Burden of Disease in Brazil: An Integrative Review (Revista Iberoamericana de Bioética, 2024)
Based on the global burden of disease, this article aims to analyze and discuss human rights vulnerabilities and violations from the perspective of health as a right. To achieve this objective, an integrative review was carried out, seeking to answer how the global burden of diseases affects individual, social and programmatic vulnerability factors, as well as human rights violations in access to healthcare for the Brazilian population. Of the 428 articles found, 119 were included in this review. The text adds analyses and reflections on the interconnected layers between individuals, their social participation networks and the institutions that should protect them, but which sometimes accentuate inequalities in access and helplessness. From this perspective, bioethics presents itself as a possible bridge to understanding the structures that expose individuals, health professionals, the community and institutions to vulnerabilities in access to health.
Keywords: public health; bioethics; access to healthcare; equity; human rights